Personnel Control Practices in Insurance Companies of Nepal - Upadhyay, Jitendra Pd (Journal of Business and Social Sciences, 2018)
Background - Personnel controlling is used to achieve best possible use of employees and their development to get the maximum benefit for the company. It will be present not only in the human resource planning and staff assessment, but also in selection, professional development, health and safety Purpose – The purpose of the study is to analyze the practices of personnel control in Insurance Companies of Nepal Methodology – Due to the specific nature of the research objectives, descriptive cum analytical research design has been used. Findings – All the insurance companies have applied the personnel control approaches in their company.